Protein adjustments in heat stressed finishing cattle - Ames, D.R.; Willms, C.L. (Kansas State University. Agricultural Experiment Station, 2011)
A summer feedlot trial indicates that protein can be removed from finishing rations in proportion to magnitude of heat stress without causing a decline in average daily lain. Cattle consumed .13 kg/hd/day (.30 lb) less supplemental protein soybean oil meal) during the 82-day period with no decline in average daily gain when compared to controls.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Protein; Heat stress; Finishing cattle